2022
DOI: 10.1186/s12871-022-01838-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of opioid-containing anesthesia versus opioid-free anesthesia using the Cortínez-Sepúlveda model on differential cytokine responses in obese patients undergoing gastric bypass surgery: a randomized controlled trial

Abstract: Background: Opioid anesthetic agents can modulate the impaired immune response in obese patients through mechanisms that involve the expression and release of cytokines. For this reason, anesthetic care for obese patients remains controversial. Therefore, the aim of the study was to compare the effect of opioid-containing anesthesia (OCA) vs opioid-free anesthesia (OFA) using the Cortínez-Sepúlveda model on IL-6, IL-1β and TNF-α serum levels before and after surgery in obese patients undergoing bypass surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The side effects of perioperative opioid use include hyperalgesia, chronic postoperative pain, respiratory depression, postoperative nausea and vomiting, or even postoperative delirium. OFA is a multimodal anesthesia strategy that combines a variety of non-opioid drugs and/or techniques to obtain high-quality anesthesia without the use of opioids 20 , 21 . A meta-analysis showed that OFA was associated with lower 24 h pain scores and risk of postoperative nausea/vomiting 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of perioperative opioid use include hyperalgesia, chronic postoperative pain, respiratory depression, postoperative nausea and vomiting, or even postoperative delirium. OFA is a multimodal anesthesia strategy that combines a variety of non-opioid drugs and/or techniques to obtain high-quality anesthesia without the use of opioids 20 , 21 . A meta-analysis showed that OFA was associated with lower 24 h pain scores and risk of postoperative nausea/vomiting 22 .…”
Section: Discussionmentioning
confidence: 99%
“…[13] OFA is a multimodal anesthesia strategy that combines a variety of non-opioid drugs and/or techniques without the use of opioids in the whole body, neuraxial or intracavitary administration during surgery to obtain high-quality anesthesia. [14,15] QLB inhibits somatic and visceral pain, producing a wide range of local anesthetic effects, while the sensory inhibition level is mostly at T7-L1, which can be used for postoperative analgesia in the abdominal and pelvic regions. [16] Pro-inflammatory markers including IL-1β, IL-2, IL-6, IL-8, IL-10, TNF-α, and CRP were measured.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Studies have shown that subjects did not have elevated serum IL-6 levels before surgery, but those who used opioid anesthesia had elevated serum IL-6 levels after surgery. [14] Compared with opioid anesthesia, OFA based on ESK has no adverse hemodynamic effects on pancreatectomy, while offering better analgesia, lower comprehensive complication index, and shorter 4-day hospital stay, without increasing the recurrence or readmission rate. [20] Clinical experiments have shown that intravenous infusion of Dex combined with ESK can reduce excessive excitation of brain neurons and alleviate the mental side effects of ESK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cortisol concentration was measured before the induction of anesthesia and then in the postoperative department; the increase was statistically significantly lower in the OFA group, which may indirectly indicate lower perioperative stress in this group of subjects [9]. Moreover, a beneficial effect of OFA on reducing immunologically mediated stress response was demonstrated in a study by Campos-Perez et al [16], in which patients in the OFA group undergoing LGB had lower interleukin 6 (IL6) serum concentrations postoperatively 13 pg/mL (5.43-22) vs. 49.58 pg/mL (18.50-112.20), respectively, p = 0.019. IL-6 is considered to be one of the most important pro-inflammatory interleukins and biomarkers of inflammation and immune activation.…”
Section: Intraoperative Nociception and Monitoringmentioning
confidence: 99%